Causes of the Resurgence of Measles and Measures to Control the Infection Based on Global and Regional Statistics - Azimovna, Berdieva Dilrabo; Orzigul, Mastonova (American Journal of Biomedicine and Pharmacy, 2025)
Measles is a highly contagious viral disease, mainly affecting children and capable of causing severe complications. In recent years, a global resurgence of measles outbreaks has been observed, primarily due to low vaccination coverage, weaknesses in healthcare systems, and global migration. This article analyzes the causes of the renewed spread of measles and discusses preventive measures and strategies for controlling the infection. The importance of vaccination, raising public awareness, and improving healthcare services to reduce disease transmission is emphasized. The article is based on global and regional statistical data and highlights the significance of international cooperation in measles prevention.